2005
DOI: 10.1111/j.1365-3040.2005.01350.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for alternative electron sinks to photosynthetic carbon assimilation in the high mountain plant species Ranunculus glacialis

Abstract: The high mountain plant species Ranunculus glacialis has a low antioxidative scavenging capacity and a low activity of thermal dissipation of excess light energy despite its growth under conditions of frequent light and cold stress. In order to examine whether this species is protected from over-reduction by matching photosystem II (PSII) electron transport (ETR) and carbon assimilation, both were analysed simultaneously at various temperatures and light intensities using infrared gas absorption coupled with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
150
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(161 citation statements)
references
References 42 publications
4
150
0
5
Order By: Relevance
“…Furthermore, Stepien and Johnson (2009) reported that PTOX acts as an alternative electron sink in the salt-stressed halophyte Thellungiella. These effects were accompanied by a significant increase in the relative abundance of PTOX in R. glacialis (Streb et al, 2005) and Thellungiella but not in Arabidopsis (Stepien and Johnson, 2009). These data support the role of IM/PTOX as an alternative electron sink in alleviating overreduction of the PQ pool under unfavorable environmental conditions where PSI is limited on the acceptor side.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Furthermore, Stepien and Johnson (2009) reported that PTOX acts as an alternative electron sink in the salt-stressed halophyte Thellungiella. These effects were accompanied by a significant increase in the relative abundance of PTOX in R. glacialis (Streb et al, 2005) and Thellungiella but not in Arabidopsis (Stepien and Johnson, 2009). These data support the role of IM/PTOX as an alternative electron sink in alleviating overreduction of the PQ pool under unfavorable environmental conditions where PSI is limited on the acceptor side.…”
Section: Introductionsupporting
confidence: 66%
“…Consequently, excitation pressure should be sensitive to both irradiance and temperature (Dietz et al, 1985;Hü ner et al, 1998Hü ner et al, , 2003Wilson et al, 2006). Since IM is considered to be a plastid terminal oxidase capable of oxidizing the intersystem PQ pool (Joë t et al, 2002;Josse et al, 2003, Aluru andStreb et al, 2005;Stepien and Johnson, 2009), we examined the effects of either changes in measuring irradiance or measuring temperature on excitation pressure in im seedlings. The data in Figure 5A illustrate the light response curves for excitation pressure in fully expanded leaves of im seedlings grown at 25/50, which results in an all green phenotype.…”
Section: Effects Of Irradiance and Temperature On Excitation Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…High light, continuous illumination, and/or low temperature were all observed to increase the proportion of closed PSII reaction centers and, therefore, the excitation pressure in the mutant and led to impaired thylakoid membrane biogenesis (Rosso et al, 2009). In several plant species, up-regulation of PTOX has been observed in response to adverse conditions, such as exposure to high-light stress in low or elevated temperature environments (Streb et al, 2005) or under salt stress (Stepien and Johnson, 2009). Deletion of the PTOX2 gene in Chlamydomonas reinhardtii, encoding PTOX, confirmed a role in preventing overreduction of the plastoquinone pool in the light (Houille-Vernes et al, 2011).…”
mentioning
confidence: 99%
“…Later, it was established that oxygen reduction can take place either downstream of PSI [leading to the so-called ''Mehler reaction'' (24)] or between PSII and PSI. The latter reaction is driven by the plastoquinol terminal oxidase (PTOX) (25), an enzyme that catalyzes electron flow from reduced plastoquinol to O 2 during the so-called chlororespiratory process (reviewed in ref. 26).…”
mentioning
confidence: 99%